Comunicação visual e comunicação sonora: uma relação semiótica: uma análise crítica, comparativa e classificatória, elaborada a partir da literatura especializada existente - Jalver Machado Bethonico (1995)
This is a study of the possibilities of establishing relationships between visual and sound communication, having an analysis of pre-existing literature as a point of departure. The study is to be carried out within the theoretical parameters of Peirce`s semiotic. Its objective is to contribute to informational science with systematized knowledge of the universe of audio-visual information transfers, in terms of communicational processes, as well as to propose possibilities of establishing the aforementioned relationships, pointing, at the same time, to deficiencies in this area of studies. The overall perspective is one of attempting to produce a body of knowledge that is instrumental for practice, which may also help meet the growing human need for communication and expression.